Thermo-Economic Comparisons of Environmentally Friendly Solar Assisted Absorption Air Conditioning Systems - Adil Al-Falahi (Applied Sciences, 2021)
Absorption refrigeration cycle is considered a vital option for thermal cooling processes. Designing new systems is needed to meet the increasing communities’ demands of space cooling. This should be given more attention especially with the increasing conventional fossil fuel energy costs and CO2 emission. This work presents the thermo-economic analysis to compare between different solar absorption cooling system configurations. The proposed system combines a solar field, flashing tank and absorption chiller: two types of absorption cycle H2O-LiBr and NH3-H2O have been compared to each other by parabolic trough collectors and evacuated tube collectors under the same operating conditions. A case study of 200 TR total cooling load is also presented. Results reveal that parabolic trough collector combined with H2O-LiBr (PTC/H2O-LiBr) gives lower design aspects and minimum rates of hourly costs (5.2 $/h) followed by ETC/H2O-LiBr configuration (5.6 $/h). H2O-LiBr gives lower thermo-economic product cost (0.14 $/GJ) compared to the NH3-H2O (0.16 $/GJ). The absorption refrigeration cycle coefficient of performance ranged between 0.5 and 0.9.